Knowledge and perceptions towards the proposed national health insurance implementation / Mohd Redhuan Dzulkipli ... [et al.] - Dzulkipli, Mohd Redhuan; Maon, Siti Noorsuriani; Jamal, Aziz; Mohammad, Mohd Fazrin; Ismail, Muazzatulamali; Imam Sarkowi, Farahin Nabilah; Ibrahim, Fadzleen (Penerbit UiTM (UiTM Press), 2018)
Public healthcare in Malaysia is largely financed by the government subsidy. With the increased demand and utilisation of healthcare services, the current financing system is seen as no longer accommodating. To maintain an agenda of universal coverage and equitable healthcare system, the government is currently proposing the implementation of national health insurance (NHI) scheme. To determine public disposition towards NHI implementation, the current study was therefore embarked. A total of 471 questionnaire copies were conveniently distributed to selected adult respondents in Klang Valley, Malaysia. Data analysis performed indicated a strong positive correlation between respondents disposition, measured by subjective norms, and attitude supporting the implementation. Increase in knowledge was also associated with positive attitude towards NHI. Result of regression analysis identified both subjective norms and knowledge contributed to the prediction of the respondents attitude.